Commons management: a reflection over the current crisis - Filipe, J. (2015)
Capitalism prevails as economic system. But often inside the system - or even emerging and going out – there are many emerging crises and there is much discussion around the system itself. Nowadays, new processes are coming to force a new vision to the economic practices. The present study presents a new vision for business and new promising ways of commitment to alternative structures but sometimes being essentially a complementary organization of society to the current standard.